Closely-coupled integration of Locata and GPS for engineering applications - Bonenberg, Lukasz Kosma (2014)
GPS has become an almost indispensable part of our infrastructure and modern life. Yet because its accuracy, reliability, and integrity depend on the number and geometric distribution of the visible satellites, it is not reliable enough for the safety of life, environmental or economically critical applications.